Digital tools to support the implementation of self-care among people with problematic substance use: An integrative literature review - Tuija Karsimus; Anna-Mari; Eeva Ekqvist; Katja Kuusisto (Finnish Social and Health Informatics Association, 2023)
Problematic substance use causes significant harm to individuals, communities and society as a whole. Nowadays solutions to bring substance abuse under control and provide help are being sought from digital tools. This literature review scrutinizes digital applications and internet-based self-care programs from the perspective of providing services. The purpose is to ascertain how the preconditions for the implementation of self-care are understood in studies addressing digital tools for the substance abuse sector. The question posed concerns what features in digital applications supporting control of substance abuse, their users and operating environment influence the implementation of self-care. The research method is an integrative literature review. The data consist of peer-reviewed scientific publications from the period 2012-2022. Data were gathered from two databases (ProQuest Central, PubMed). The final corpus comprises 18 research articles. The analytical frame of reference is the definition by El-Osta and others of four main dimensions of self-care. The findings suggest that factors pertaining to applications in the implementation of self-care are the technical usability of the service, the option for anonymity, variation in content, active reminders and application feedback, gamification and ability to identify with the user. Factors pertaining to the users, in addition to age and gender, are mode of substance abuse, duration of using history, severity of the problem, readiness for change, possible concurrent diagnoses, ability to process own feelings, social relations and digital literacy. Factors pertaining to the operating environment are legislation governing substance abuse, national intoxicant culture, stigma attached to substance abuse treatment, availability of support outside the application and the pandemic situation restricting face-to-face interaction. The diverse nature of the group of individuals with problematic substance use will in the future increase the need for user profiling and more individualized tailoring of application content in keeping with their life situations and stages of recovery.